1999
DOI: 10.1023/a:1006125229477
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A 1369 bp DNA fragment (Sc) was isolated from a full-length clone of sugarcane bacilliform badnavirus (ScBV) and was shown to have promoter activity in transient expression assays using monocot (banana, maize, millet and sorghum) and dicot plant species (tobacco, sunflower, canola and Nicotiana benthamiana). This promoter was also tested for stable expression in transgenic banana and tobacco plants. These experiments showed that this promoter could drive high-level expression of the beta-glucuronidase (GUS) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The activity of SCBV21 in monocots and dicots was evaluated by adopting a transient gene expression assay, previously shown to be rapid, quantifiable, and reproducible for the comparative analysis of the activity of different promoters [34, 41]. Transient and stable expression analyses using SCBV21 fusions to EYFP and GUS genes ( SCBV21:EYFP and SCBV21:GUS ) showed that the promoter is functional in both monocots (sugarcane and sweet sorghum) and dicots ( N. benthamiana and lima bean), consistent with the activity of the SCBV promoters from SCBMOV-MOR [19, 20, 30, 56] and SCBIMV-QLD species [57]. …”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The activity of SCBV21 in monocots and dicots was evaluated by adopting a transient gene expression assay, previously shown to be rapid, quantifiable, and reproducible for the comparative analysis of the activity of different promoters [34, 41]. Transient and stable expression analyses using SCBV21 fusions to EYFP and GUS genes ( SCBV21:EYFP and SCBV21:GUS ) showed that the promoter is functional in both monocots (sugarcane and sweet sorghum) and dicots ( N. benthamiana and lima bean), consistent with the activity of the SCBV promoters from SCBMOV-MOR [19, 20, 30, 56] and SCBIMV-QLD species [57]. …”
Section: Discussionmentioning
confidence: 78%
“…The extensive genetic diversity of SCBV has been reported in the promoter [57], RT/RNase H [29], and full genomic [25] sequences. In this study, we cloned, mapped, and functionally characterized a novel SCBV promoter, SCBV21 , in addition to two SCBV promoters previously developed from SCBIMV-QLD [57] and SCBMOV-MOR [19, 20]. SCBV21 shared low nt sequence identity with the published SCBIMV-QLD and SCBMOV-MOR promoters, respectively based on the full promoter sequence, showing that it is a distinct promoter [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modification by adding introns or enhancers containing fragments from either monocots or dicots improve the utility of CaMV promoter in transformation systems of maize and bluegrass (Vain et al 1996). SCBV promoter from the plant virus, sugarcane bacilliform virus, is active in monocots (Tzafrir et al 1998), and has been shown to drive high levels of gene expression in banana (Schenk et al 1999, 2001), sugarcane (Braithwaite et al 2004) and maize (Davies et al 2014). …”
Section: Introductionmentioning
confidence: 99%